SARS-COV2 infection in heart transplant patients. : Case report - Yarahuaman Mora, Jhoel Braiyn (2020)
Since the first reports of SARS-CoV-2 infection in December 2019 in Wuhan, China, we have witnessed its worldwide spread, and the serious complications it caused in thousands of patients. Recipients of solid organ transplants are among the risk population due to immunosuppression. There is lack of information about the presentation, clinical course, management, and prognosis of coronavirus disease (COVID-19) in these patients. We present 2 cases of heart transplant recipients who contracted SARS-CoV-2 infection and received treatment in a Cardiology Institute in Lima, Peru.